Peningkatan Potensi Pangan Fungsional Nugget Daging Kelinci Dengan Penambahan Rumput Laut - Syadad Ali; Fani Evadewi; Supranoto Supranoto; Wida Nurnaningsih (Fakultas Peternakan. Unwiku, Purwokerto, 2025)
The research titled The Effect of Lemon Juice Addition on Texture and Color of Goat Milk Yogurt, was conducted at the Laboratory of the Faculty of Animal Husbandry, Wijayakusuma University, Purwokerto, on June 26–27, 2024. This study aimed to determine the effect of varying levels of lemon juice on the texture and color of goat milk yogurt. Materials used included 1000 ml of goat milk, 50 ml of yogurt starter, and 63 ml of lemon juice. The method applied was an experimental approach using a Completely Randomized Design (CRD) with a one-way pattern. The study consisted of 4 treatments and 25 replications. The treatments were: P0 (no lemon juice), P1 (1% lemon juice of total yogurt volume), P2 (2%), and P3 (3%). Organoleptic tests on texture and color were conducted by 25 semi-trained panelists. Data were analyzed using variance analysis, followed by the Least Significant Difference (LSD) test. The results showed that lemon juice addition had a very significant effect (P<0.01) on both the texture and color of the yogurt. The increase in lemon juice concentration enhanced the visual appeal and altered the texture, indicating its potential role in improving yogurt quality